2022
DOI: 10.3389/fpubh.2022.864861
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of a Diagnostic and Counseling Service for People Living With HTLV-1/2 in a Metropolis of the Brazilian Amazon

Abstract: IntroductionTo identify the prevalence of infection in the urban area of the capital city of Belém, Brazil, the Laboratory of Virology of the Federal University of Pará implemented, as a public service, serological screening for human T-lymphotropic viruses 1 and 2 (HTLV-1/2) infection and, if necessary, counseling service and referral to specialized medical care. The project is funded by the National Council of Science and Technology, the Ministry of Health of Brazil and the Pan American Health Organization.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Along with targeted screening of pregnant women, blood donors, and people who attended clinics for sexually transmitted infection, once-in-life testing has been suggested for HTLV-1, as recommended for HIV and hepatitis B and C [ 27 ]. Concerns have been raised about the need to provide information about transmission-preventive measures for people living with HTLV-1/2 [ 28 ]. Studies are also required on HTLV-1 transmission and HIV pre-exposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Along with targeted screening of pregnant women, blood donors, and people who attended clinics for sexually transmitted infection, once-in-life testing has been suggested for HTLV-1, as recommended for HIV and hepatitis B and C [ 27 ]. Concerns have been raised about the need to provide information about transmission-preventive measures for people living with HTLV-1/2 [ 28 ]. Studies are also required on HTLV-1 transmission and HIV pre-exposure prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…A low prevalence of HTLV-1 and HTLV-2 among the quilombola population has been described, ranging from 0.11 to 2.6% and 0.34 to 1.06%, respectively [ 32 , 33 ]. In the urban region of Belém, the rates are usually higher, ranging from 0.19 to 2% [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], as well as in a group of people living with HIV [ 35 ], blood donors [ 17 ], and sex workers [ 36 ], while in pregnant women, this prevalence is considerably lower [ 16 ]. In the Pará region, a high prevalence of HTLV-2 is usually described among indigenous populations because they are closed communities [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that Brazil has the highest number of absolute cases of HTLV infection, with approximately 800,000 to 2.5 million people infected [ 9 , 10 ], and epidemiological studies have already demonstrated the presence of this virus in several areas such as São Paulo [ 11 ], Santa Catarina [ 12 ], Salvador [ 13 ], and Pará [ 14 ], as well as other states. Maranhão, Bahia and Pará have high prevalence rates of the virus, as indicated in studies performed in blood donors, in pregnant women or in the general population [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation